The Vote of Silence: The Problem of Abstention in Municipal Elections in Mozambique - Baloi, Jochua AbrÃ£o (Budapest International Research and Critics University, 2019)
This article analyzes the problem of absenteeism in the municipal elections in Mozambique, specifically analyzing Matola municipality in Maputo province. The central argument of this article is that the electoral absenteeism is a form of political questioning in order to demonstrate the dissatisfaction and protest of the electoral process per se. Most representative western democracies and Mozambique in particular, have experienced in recent times a higher percentage of abstention in electoral process. This phenomenon is due to the transformation of the way of understanding political participation through voting, which denotes the lack of political culture of elections. Therefore, it is concluded that in order to minimize the absenteeism in Matola municipality it is necessary to create a favorable institutional environment, where the citizens will feel the effect of their vote that guarantees them the exercise of citizenship.